A, KEBERPIHAKAN GEREJA TERHADAP PARA PENYANDANG DISABILITAS DI WILAYAH TERITORI II KLASIS KUPANG TENGAH GEREJA MASEHI INJILI DI TIMOR - Daud Saleh Luji; Hemi D. Bara Pa; Kristian E.Y.M. Afi (Ra'ah: Journal of Pastoral Counseling, 2021)
The purpose of this article is to find out how the Evangelical Christian Church in Timor, especially the Congregations in Territory 2 Klasis Kupang Tengah, takes sides with persons with disabilities. The method used in this research is a qualitative method by interviewing six people with disabilities and triangulation of sources to a number of pastors who have members of the congregation with disabilities. From the results of the research, it was found that the church has not taken sides with members of the congregation with special needs or disabilities because spiritual services in terms of visiting and praying for people with disabilities have not been carried out properly, the Church has never provided special assistance for people with disabilities. Skills training or working capital assistance has not been carried out, there is no access to worship, namely providing access to the church building for wheelchair users. Persons with disabilities have not been involved in court service programs and RAPBJ and persons with disabilities have not been given space to be involved in categorical and functional services.